Evaluation of Fire Risks to Improve Safety in the Operating Room - Rodovich, Lisa (My University, 2018)
Background: Patient safety is the cornerstone of high-quality health care, and has become an increasingly important public concern. Surgical fires are a preventable, never event. As with other low incidence but high impact events, solutions to prevent this complication are known and published. However, preventive measures have yet to diffuse sufficiently across professional boundaries. The challenges to preventing fires relate to educating all of the members of the surgical team, and overcoming barriers to intraoperative communication. Methodology: Through an educational program, the surgical services staff at the selected facility were made aware of the importance of acknowledging fire safety through the implementation of a fire risk assessment with every procedure. Use of the fire safety checklist was monitored for compliance. Findings: Results showed a 95% compliance rate with checklist completion, and 90% effective communication of the fire risk score to members of the surgical team. Feedback was positive throughout, including making the process concise, quick, and easy to complete, as well as improving communication among team members.
Keywords: Patient safety, surgical fires, surgical safety checklists, preventing OR fires, fire safety, fire risk assessment checklist